2021
DOI: 10.1186/s12931-021-01655-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia promoted lung cancer stem cell-like properties via enhancing Bach1 expression

Abstract: Background An adverse role for obstructive sleep apnea (OSA) in cancer aggressiveness and mortality has recently emerged from clinical and animal studies, and the reasons have not been fully determined. Cancer stem cells (CSCs) are regarded as the main cause of carcinoma metastasis. So far, the relationship between OSA and lung CSCs has not been explored. Method In the present study, we established an orthotopic mouse model of primary lung cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…However, the specific mechanisms underlying the elevation of Bach1 in lung CSCs have yet to be investigated. Previously, we reported that chronic intermittent hypoxia induced lung cancer stem cell-like properties through enhancing Bach1 expression [ 29 ]. In addition, we would further check the detailed mechanism that Bach1 induces lung tumor growth and reduces lung cancer cell death.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific mechanisms underlying the elevation of Bach1 in lung CSCs have yet to be investigated. Previously, we reported that chronic intermittent hypoxia induced lung cancer stem cell-like properties through enhancing Bach1 expression [ 29 ]. In addition, we would further check the detailed mechanism that Bach1 induces lung tumor growth and reduces lung cancer cell death.…”
Section: Discussionmentioning
confidence: 99%
“…RR, risk ratio. exacerbate tumor progression, aggressiveness, and metastasis via multiple molecular mechanisms in lung cancer (Guo et al, 2019;Kang et al, 2020;Torres et al, 2020;Hao et al, 2021), experimental studies regarding the role of intermittent hypoxia on the pathogenesis of lung cancer remain lacking. Future studies are warranted for improving the understanding of the mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…An important example of this association between cancer and the cyclic hypoxia might be appreciated in cancer patients suffering from obstructive sleep apnea (OSA); this association participates in increasing the incidence and mortality of cancer [ 33 ]. Several studies have confirmed that exposure to cyclic hypoxia increases cancer stem cell markers, as well as features related to metastasis [ 34 , 35 , 36 ]. It has even been suggested that the aggressiveness in melanoma can be mediated by TGF-β (a well-known pro-fibrotic cytokine) [ 37 ].…”
Section: Cancer Hallmarks Associated With Hypoxiamentioning
confidence: 99%